Hydrogen from glycerol steam reforming with a platinum catalyst supported on a SiO2-C composite - Buffoni, Ivana Natalia (2017)
This work studies 2 wt% Pt catalysts. The support is a SiO2-C composite whose main features are a high specific surface due to its mesoporosity, a higher thermal stability than the C support, and the absence of surface acid sites which could promote the dehydration reactions that produce coke precursors. The Pt/SiO2-C catalyst has very small metallic particles (dva = 1.37 nm) that favor the C-C bond cleavage reactions which allow obtaining total gas conversion at 450C. With this catalyst, it is possible to obtain high yields to H2, between 4 and 5, which indicates that the active sites promote the WGS reaction, even with glycerol concentrations of 30 and 50%. Pt/SiO2-C is a very stable catalyst since it loses only 10% of its initial activity after 66 h on stream and is resistant to sintering and coke deposition.